Effects of the islamic values of entrepreneurs in information technology industry - Baharun, Rohaizat; Abdul Rahman, Ismail (Universiti Teknologi Malaysia, 2000)
This study examines the effect of Islamic values of Muslim entrepreneurs in business activities and reports the findings from a study of information technology companies. The aim of this study is to contribute to the understanding of entrepreneurship in information technology companies by adopting a perspective which has not been considered in previous studies of entrepreneurship. Unlike in existing research, religious practices in Islam were tested to seek the relationship between religious values and business performance.